California 2024 - Charmei, Amber; Edwards, Maria (Travel writer); Patten, Carolyn; Voormeij, Lisa (Eyewitness travel guides., 2024)
A guide to California that outlines its culture and history, offers profiles of the major cities, describes sightseeing attractions, and recommends hotels, restaurants, shopping, and outdoor activities.